Exploring the Photochemistry of an Ethyl Sinapate Dimer: An Attempt Toward a Better Ultraviolet Filter - Horbury, Michael D.; Turner, Matthew A. P.; Peters, Jack S.; Mention, Matthieu; Flourat, Amandine L.; Hine, Nicholas D. M.; Allais, Florent; Stavros, Vasilios G. (Frontiers in Chemistry, 2020)
The photochemistry and photostability of a potential ultraviolet (UV) radiation filter, dehydrodiethylsinapate, with a broad absorption in the UVA region, is explored utilizing a combination of femtosecond time-resolved spectroscopy and steady-state irradiation studies. The time-resolved measurements show that this UV filter candidate undergoes excited state relaxation after UV absorption on a timescale of ~10 picoseconds, suggesting efficient relaxation. However, steady-state irradiation measurements show degradation under prolonged UV exposure. From a photochemical standpoint, this highlights the importance of considering both the ultrafast and “ultraslow” timescales when designing new potential UV filters.